Learning provides mating opportunities for males of a parasitoid wasp. Issue 3 (21st October 2013) - Danci, Adela; Hrabar, Michael; Ikoma, Shari; Schaefer, Paul W.; Gries, Gerhard
Abstract The ability of insects to learn locations of future resources has rarely been studied. Here, we show that males of the solitary parasitoid wasp Pimpla disparis Viereck (Hymenoptera: Ichneumonidae) learn locations of future mates. Male P. disparis reportedly arrest on parasitized pupae of wax moth, Galleria mellonella L. (Lepidoptera: Pyralidae), and gypsy moth, Lymantria dispar L. (Lepidoptera: Erebidae), when mate emergence is imminent. We tested the hypothesis that male P. disparis identify, memorize, and revisit the location(s) of parasitized host pupae as a strategy to attain mates. We colour‐coded P. disparis males in the field and noticed that they revisit parasitized moth pupae on consecutive days, and arrest on those pupae with a near‐emergence P. disparis parasitoid. In a laboratory experiment with two large corrugated cardboard cylinders (CCCs) as surrogate trees, each CCC bearing two parasitized moth pupae with a near‐emergence P. disparis parasitoid or two pupae not parasitized, males on day 1 of the experiment visited parasitized pupae more often than pupae not parasitized. On day 2, when each CCC had been replaced and now carried pupae that were not parasitized, males returned to the same CCC, or the same micro‐location on that CCC, which on day 1 had carried parasitized pupae. Field and laboratory data combined indicate that male P. disparis learn the location of future mates. With female P. disparis being haplodiploid and capable of reproducing without mating experience, the onus to find a mate is on males. They accomplish this by detecting parasitized pupae, learning their location, revisiting them frequently, and then arresting on them when the prospective mate nears emergence, taking a 50% chance that it is indeed a female.